(3GdOQQ GdSGWYI aj GdCOhjI GdbGWYIs - (3eMeO Hf EHQGgje Hf jhSa GdMdHj GdbGOQj GdJGPaj, QVj GdOjf GHf GdMfHdj, jJUd fSHg HGHf GdTMfI,J (B971 (3g` s
(3ChdgG (B:s
(3SCdfi HYV ENhGfi Cf CDda dge eNJUQkG ai Yde GdWH hbO GQOJ fXe HQA SGYI ai YbO OQ cGed GdUfGYI s
(3BNQgG (B:s
(3Cjf CfJ ef EHGf GdTaGA , acja CHhg GdCjGJ ai EfGA aSbGgG dhdOI aHQF ai GdMjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B302 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B223s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B42) s
Keywords: (3GdWHs